2018
DOI: 10.1016/j.bja.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of arterial hypotension after spinal anaesthesia using vena cava ultrasound to guide fluid management

Abstract: www.clinicaltrials.gov - NCT02271477.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 35 publications
(22 reference statements)
2
61
0
1
Order By: Relevance
“…The IVCCI had high specificity and low sensitivity in experiments by Mueller et al when a cutoff level of >40% was used to predict volume responsiveness [14]. However, this performance as a diagnostic tool is, on the one hand, similar to that observed in our experiments in the case of the value of 50%, but on the other hand, Mačiulienė et al failed to detect a prognostic role of the IVCCI [19], while another recent trial reported an IVCCI-based fluid replacement strategy as a useful tool to reduce the incidence of hypotension [20].…”
Section: Discussionsupporting
confidence: 86%
“…The IVCCI had high specificity and low sensitivity in experiments by Mueller et al when a cutoff level of >40% was used to predict volume responsiveness [14]. However, this performance as a diagnostic tool is, on the one hand, similar to that observed in our experiments in the case of the value of 50%, but on the other hand, Mačiulienė et al failed to detect a prognostic role of the IVCCI [19], while another recent trial reported an IVCCI-based fluid replacement strategy as a useful tool to reduce the incidence of hypotension [20].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, people whose fluid therapy was guided by CVCCI evaluation had a 35% relative risk reduction in the development of hypotension. 22 In a recent meta-analysis evaluating the CVCCI capability to predict fluid responsiveness in spontaneously breathing human patients, CVCCI showed moderate accuracy with a pooled sensitivity of 0.80 (95% CI, 0.68 to 0.89) and a pooled specificity of 0.79 (95% CI, 0.60 to 0.90). In patients undergoing mechanical ventilation, the pooled sensitivity and specificity were 0.79 (95% CI, 0.67 to 0.86) and 0.70 (95% CI, 0.63 to 0.76), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Mačiulienė et al failed to detect the prognostical role of IVCCI [17], while another recent trial reported an IVCCI based fluid replacement strategy as a useful tool to reduce the incidence of hypotension [18].…”
Section: Discussionmentioning
confidence: 99%